Pemetaan Perubahan Biodiversitas Hutan Rawa Gambut Berbasis Citra Penginderaan Jauh Di Sub DAS Rungan Kalimantan Tengah: Mapping of Peat Swamp Forest Biodiversity Changes Based on Landsat 8 Imagery at Rungan Sub Watershed Central Kalimantan - Sukarna, Raden Mas; Rotinsulu, Johanna Maria; Sampang, Sampang; Nuwa, Nuwa; Triyadi, Antonius; Nursiah, Nursiah (JURNAL HUTAN TROPIKA, 2025)
Monitoring changes in peat swamp forest biodiversity is a necessity for identifying and accounting for the impacts of various factors that cause degradation and deforestation. Information on the condition of this biodiversity can be obtained using Landsat 8 Imagery. This imagery allows for a more efficient, effective, and systematic analysis of changes in vegetation density. This study aimed to assess the dynamic changes in peat swamp forest biodiversity over approximately the last 10 years. The research findings indicate that the rates of degradation and deforestation (16.86%) are higher than the rate of regrowth (6.27%)5. This suggests that the ecosystem's condition is experiencing a significant decline. This decline is characterized by a tendency for the diversity, richness, and evenness of flora species to decrease. The study concludes that the floristic dynamics at the Rungan sub-watershed have declined, which can also affect the existence and habitat of its fauna.